2018
DOI: 10.1039/c7ee02723k
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid electrolytes with 3D bicontinuous ordered ceramic and polymer microchannels for all-solid-state batteries

Abstract: A novel templating method to create 3D bicontinuous structured hybrid electrolytes with improved mechanical properties for all-solid-state lithium batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
208
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(230 citation statements)
references
References 36 publications
1
208
1
Order By: Relevance
“…[27] Recently,H u's group traced the Li + transporting pathway by monitoring the replacement of 7 Li in the HSSE by 6 Li with high-resolution nuclear magnetic resonance (NMR). [40] Reproduced with permission. [28c] As the amounto fL LZO phase increases, the ion transport pathway transfers from polymer to inorganic component, accompanied by decrease of ion mobility and increaseo fa ctive ion concentration.…”
Section: Composite Polymer-inorganic Hssesmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] Recently,H u's group traced the Li + transporting pathway by monitoring the replacement of 7 Li in the HSSE by 6 Li with high-resolution nuclear magnetic resonance (NMR). [40] Reproduced with permission. [28c] As the amounto fL LZO phase increases, the ion transport pathway transfers from polymer to inorganic component, accompanied by decrease of ion mobility and increaseo fa ctive ion concentration.…”
Section: Composite Polymer-inorganic Hssesmentioning
confidence: 99%
“…[37] As showni nF igure 4c,t he flexible HSSE is formed by filling LiTFSI-PEO into the porous3 D LLZO skeleton, possessing an ionic conductivity of 2.5 10 À4 Scm À1 at room temperature as ar esult of the interconnectedl ithium conducting channels. [40] Four microarchitectures (cube,g yroid, diamonda nd bijel-derived) were investigated as 3D printing templates to produce PEO-LAGPH SSEs with different structures, among which gyroid PEO-LAGPe lectrolyte demonstrates the best combinationo fc onductivity and mechanical properties. Recently,3 Dc onnected necklace-likeL ATPw ith poly(ethylene glycol) diacrylate (PEGDA) and poly(dimethylsilone) (PDMS)h as been constructed by applying externalalternating-current electric field.…”
Section: Composite Polymer-inorganic Hssesmentioning
confidence: 99%
“…For example, Li + conducting fillers such as Li 7 La 3 Zr 2 O 12 and Li 1.5 Al 0.5 Ti 1.5 (PO 4 ) 3 were found to have more pronounced effect in improving the ionic conductivity than inactive fillers. For example, Li + conducting fillers such as Li 7 La 3 Zr 2 O 12 and Li 1.5 Al 0.5 Ti 1.5 (PO 4 ) 3 were found to have more pronounced effect in improving the ionic conductivity than inactive fillers.…”
mentioning
confidence: 99%
“…[25][26][27][28][29][30][31] Controlling the size of the fillers is definitely important as it is related to the effective fillerpolymer interaction interface area. [3,10,[34][35][36] Compared to nanoparticles and nanowires, using 2D fillers for SPE was rarely reported. It is reported that aligned nanoparticles and nanowires in solid composite electrolytes could enhance the ionic conductivity than randomly dispersed fillers.…”
mentioning
confidence: 99%
“…9c), along with improved mechanical properties imparting the ability to block dendrite grow thin a symmetric Li cell during repeated Li stripping/plating processes. More recently, Bruce et al [174] created a 3D bi-continuous structured hybrid electrolyte with improved mechanical properties using a template method (Fig. 9d).…”
Section: Shapes Of Inorganic Fillersmentioning
confidence: 99%